Determining Packaging Elements by Kansei Engineering Approach of Salt Bread Products - Sari, Novi Purnama; Wijayanto, Ardy Surya; Yanti, Novia Andri; Salsabila, Thalia (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2000)
Packaging has a crucial role in a product and is an important aspect in attracting consumer attention to buy a product. Packaging design elements serve as a key visual medium to describe product characteristics. Salt Bread products have not optimized the design elements in their packaging, so packaging development is needed. This research aims to determine design elements based on consumer preferences. This research uses the Kansei Engineering method to obtain design elements that align with the design concept that has been generated. Utilizing of the QTT1 method to produce packaging design elements for Salt Bread products. Determination of design elements is done by distributing Likert questionnaires to assess the suitability of the design concept with 53 packaging samples. The resulting design concept, namely “Minimalist-Attractive”. The results of running QTT1 data with R software obtained design elements, namely art carton material (X1.2), medium size (X2.2), square cube shape (X3.4), interlocking lid (X4.6), window and tray features (X5.6), classic elegant design style (X6.8), and direct printing and paper indirect printing techniques (X7.3). The resulting elements on the Salt Bread packaging are in line with the packaging design concept according to consumer preferences.